Non-operative functional treatment for acute Achilles tendon ruptures: The Leicester Achilles Management Protocol (LAMP). Issue 4 (April 2019) - Aujla, Randeep S.; Patel, Shakil; Jones, Annette; Bhatia, Maneesh
Highlights: An 8-week dynamic functional regime can be used to treat the majority of acute Achilles tendon ruptures. Immediate full-weight bearing does not impair outcomes or re-rupture rate. 2% re-rupture rate and functional scores of 76/100. Low complications can be expected. Abstract: Objectives: The purpose of this study is to present outcomes and objective measures of assessment for acute Achilles tendon (AT) ruptures treated with an eight-week functional dynamic treatment protocol in a VACOped® boot with immediate full weight bearing mobilisation, the Leicester Achilles Management Protocol (LAMP). Methods: A prospective study of all patients treated with the LAMP with minimum 12-month follow-up was performed. Patients completed the Achilles Tendon Rupture Score (ATRS) and in the latter part of the study, objective measures of the calf muscle girth and heel raise height were obtained. Results: 442 patients were treated with the LAMP. There were nine (2%) re-ruptures in the 442 non-operative treated group of patients throughout the study period. ATRS at twelve months or more were available in 234 patients and objective measures in 77 patients. The mean age was 50 years. The mean ATRS was 75.5 at an average of 23 months post injury. Men had a statistically significant higher ATRS score when compared to women (p < 0.05). There was statistically significant difference in the calf muscle girth and the heel raise height when compared to the uninjured side at 12-months post-injury (p < 0.05). These differences did not correlate with the ATRS (p > 0.05). Conclusions: The LAMP is a simple yet effective regime for the non-operative treatment of acute AT ruptures, which can be universally adopted without the need for many resources. Compared to other studies, the overall time in the boot is less with low complication rates and similar patient reported outcomes.